ANALISIS HASIL BELAJAR KOGNITIF MAHASISWA PADA PERKULIAHAN STRATEGI PEMBELAJARAN FISIKA BERPOLA LESSON STUDY - Hikmawati, Hikmawati; Kesipuddin, Kesipuddin; Rahayu, Satutik (Lensa : Jurnal Kependidikan Fisika, 2014)
The purpose of this study was to analyze the students' cognitive learning outcomes in the lesson study of Physical Learning Strategy. The subjects of the study consisted of 62 students at the Physics Learning Physics Year 2013/2014 at FKIP UNRAM. The pattern of lesson study has been done for two cycles. Each cycle consists of three stages: plan, do, see. At the end of each cycle has been given a test to determine the level of mastery of student competence. The results showed that there was an increase in cognitive learning outcomes from cycle I to cycle II. In the first cycle evaluation (Cooperative learning model) obtained an average score of 71 (grade B) and on the second cycle (Problem-Based Learning Model) obtained an average score of 77 (grade B +). Therefore, the lesson study pattern needs to be developed as a way to improve the quality of education that never ends (continuous improvement).